An experimental and computational analysis of compressor cascades with varying surface roughness - Fouflias, Dimitrios (Cranfield University, 2009)
This thesis presents a CFD and experimental analysis associated with the parameter compressor fouling and a CFD analysis associated with the parameter on-line compressor washing of industrial gas turbines. On-line compressor washing is very popular and quite effective in the industrial gas turbine operational scheme. Many companies apply on-line washing with the engine running at normal speed so as to avoid downtime periods for off-line cleanings that could cause significant economic drawbacks. At this thesis vital parameters affecting compressor cleaning of an industrial gas turbine were examined and combined in such a way so as to provide adequate coverage of the frontal inlet guide vane area which is critical for effective cleaning. The parameters investigated were water injection nozzle position, inclination with respect to the engine centerline, injection velocity and nozzle spray angles. However, before applying compressor washing, compressor fouling comes into consideration. For this purpose a compressor cascade tunnel (test rig) was designed and come into operation in order to examine different levels of fouling. The cascade test rig involved as well a washing kit for future cleaning of the cascade blades. This work related to the cascade design released a lot of information about designing suction type compressor cascade test rigs by analysing the flow inside the cascade rig computationally and three-dimensionally via CFD tools. The results in terms of the quality of flow obtained for the current test rig were also compared with modified versions of the test rig, one which involved a bigger plenum area behind the cascade test section and one involving the current rig running in a blowing type mode. The CFD results coming out from the compressor cascade tunnel for the different fouling levels, were analysed in terms of mass flow capacity and polytropic efficiency reduction due to fouling by using Howell’s theory (1945) and they were used as inputs for running performance simulation in terms of an industrial gas turbine engine using the performance simulation code Turbomatch. Therefore, a correlation between cascade fouling and real engine uniformly stage spread fouling was achieved. At high levels fouling where the 254 microns roughness height takes place, the nondimensional air mass flow reduction can reach levels of 1.6% and the drop in compressor efficiency can touch the value of 5%. The CFD results obtained after running all the simulation scheme for the different roughness levels, were compared to the actual experimental results coming from running the compressor cascade rig with the same fouling scheme of roughness. Applying Howell’s theory (1945), the fouled cascade was correlated to a uniformly fouled stage and a real industrial gas turbine. This time input in the Turbomatch code was the percentage deterioration in compressor efficiency calculated from correlated cascade data. This deterioration reaches a high level of 11 % when the fouling particle size is 254 microns.